Symmetrical Information Disclosure for Investors’ Investment Decisions - Abu Hasan, Norraidah; Azuddin Yakob, Noor; ., . (International Journal of Engineering and Technology, 2018)
Information disclosure is crucial in the financial market that allow investors to understand the current and future performance of companies and help them in their investment decisions. This paper aim to examine the importance of information disclosure to safeguard the investor investment. This paper will refine the theoretical background of agency theory associated with the information disclosure. The findings of this paper provide a new dimension of symmetrical information disclosure with the aim to sustain a firm in the financial market and enhance investors’ confidence.